Prevalence of electrocardiographic abnormalities in primary care patients according to sex and age group. A retrospective observational study - Santos, Julia Pereira Afonso dos; Ribeiro, Antonio Luiz Pinho; Andrade-Junior, Diomildo; Marcolino, Milena Soriano (São Paulo Medical Journal, 2018)
BACKGROUND: Knowledge of the prevalence of electrocardiographic abnormalities in a population is useful for interpreting the findings. The aim here was to assess the prevalence of electrocardiographic abnormalities and self-reported comorbidities and cardiovascular risk factors according to sex and age group among Brazilian primary care patients. DESIGN AND SETTING: Observational retrospective study on consecutive primary care patients in 658 cities in the state of Minas Gerais, Brazil, whose digital electrocardiograms (ECGs) were sent for analysis to the team of the Telehealth Network of Minas Gerais (TNMG). METHODS: All ECGs analyzed by the TNMG team in 2011 were included. Clinical data were self-reported and electrocardiographic abnormalities were stratified according to sex and age group. RESULTS: A total of 264,324 patients underwent ECG examinations. Comorbidities and cardiovascular risk factors were more frequent among women, except for smoking. Atrial fibrillation and flutter, premature beats, intraventricular blocks, complete right bundle branch block and left ventricular hypertrophy were more frequent among men, and nonspecific ventricular repolarization abnormalities and complete left bundle branch block among women. CONCLUSION: Electrocardiographic abnormalities were relatively common findings, even in the younger age groups. The prevalence of electrocardiographic abnormalities increased with age and was higher among men in all age groups, although women had higher frequency of self-reported comorbidities.